Asymptotic Stability for Coupled Modal Sliding Mode Control of Vibration in a Flexible Structure - Ming-Chang Pai; Alok Sinha (Shock and Vibration)
This paper deals with the asymptotic stability of the coupled modal sliding mode control of a vibratory structure in the presence of parametric uncertainties. The method is based on the linear fractional transformation and the small gain theorem / μ analysis. Using a flexible tetrahedral truss structure, a numerical example is presented to verify the theoretical analysis.